Effectiveness of HAPA-based multidomain fall risk management for older adults with declining intrinsic capacity in nursing homes: protocol of a randomised controlled trial - Jing Yang; Qinghua Zhang; Mei Cheng; Siyi Shang; Shengguang Cheng; Lingxia Qi; Tongtong Liu; Yuhan Yang; Xinuo Yao; Danyan Lu; Xiaoyu Cheng (BMJ Open)
Introduction Accidental falls are a common geriatric syndrome that hinders healthy ageing in older adults. Older adults who live in nursing homes (NHs) are at a greater risk of accidental falls than those who reside in communities. Intrinsic capacity (IC) decline has been shown to be an independent influencing factor for fall risk. Moreover, healthy behaviour is a prerequisite for IC. Therefore, this study considers IC as a starting point, with an aim of developing, implementing and evaluating a low-administration-cost multidomain fall risk management intervention programme based on the Health Action Process Approach.Methods and analysis The target population includes older adults with declining IC in Chinese NHs. A random lottery method will be adopted to divide the 100 participants into the control group and intervention group. The project will be conducted in three parts over 24 weeks. In the first part, a fall risk management intervention pathway and programme will be developed with the theoretical and IC framework, which will be refined via the Delphi method. In the second part, a randomised controlled trial will be implemented. The control group will receive usual care and health education, and the intervention group will complete a three-stage process to complete fall risk management behaviour intention and behaviour maintenance. In the third part, follow-up will be conducted to clarify the maintenance effectiveness of the programme in fall risk management. Behaviour change techniques and an interactive handbook will be used to increase the feasibility of the programme. The primary outcomes will include the IC composite score (cognition, locomotion, vitality, sensation and psychology) and fall risk. The secondary outcomes will include gait and balance, strength, fall efficacy, fall prevention self-management, fall management behaviour stages and healthy ageing. The outcomes will be assessed at baseline, and then after 4 weeks, 16 weeks and 24 weeks in both groups. The effectiveness of the intervention will be analysed via linear mixed models on a range of outcomes.Ethics and dissemination The trial was approved by the Huzhou University Committee (No.2023-06-06). The results will be submitted for publication in a peer-reviewed journal and presented at conferences.Trial registration number NCT05891782.